The A Comparative Study of Name Significance in Shakespeare's Romeo and Juliet and Wilde's Earnest.: A Comparative Study Mariwan Hasan - Hasan, Mariwan (LPPM Universitas Advent Indonesia, 2025)
In literary discourse, names frequently transcend their conventional role as mere identifiers, emerging as profound symbols of thematic constructs such as identity, societal expectations, and personal values. This dynamic is vividly illustrated in William Shakespeare's Romeo and Juliet and Oscar Wilde's The Importance of Being Earnest, each of which employs the concept of names to engage with and critique different societal facets. Shakespeare's approach intertwines names with the thematic exploration of tragic consequences stemming from entrenched familial feuds and rigid social constraints. The protagonists' names in Romeo and Juliet are emblematic of their entangled fates and the destructive nature of inherited animosities, serving to underscore the broader implications of identity and societal division. Conversely, Wilde’s satirical lens in The Importance of Being Earnest utilizes names to critique the superficial values and social pretensions of Victorian society. In Wilde's play, the adoption of false identities and the ensuing comedic conflicts expose the absurdities inherent in societal norms and personal deceptions. This essay will analyze how both Shakespeare and Wilde utilize names as critical instruments for reflecting and critiquing societal norms, relational dynamics, and individual identities. This analysis will be supported by textual evidence and scholarly interpretations, elucidating the distinct approaches each playwright employs in their respective works.